Sistem Informasi Akuntansi Pembelian Bahan Baku untuk Proyek - Cristian, Lianawati; Meutia, D. (Bina Nusantara University, 2012)
Along with the development of technology, every line of business as well as a company that specializes in a construction project requires an information system that can support the company’s operations. The research objective is to analyze, identify the information needs, improve and design an accounting information system of construction materials purchases needed by the management of a contractor company to assist in decision making and address the issues contained in the running system. The research is carried out byimplementing data collection and information, analysis on the running system, analysis of research findings, identification of information needs, and identification of system requirements, as well as a structured design ofobject oriented analysis design (OOAD) and unified modeling language (UML). The result obtained is an improving application design that features document numbering, document filing, and reports. The newdesigned accounting information system of raw material purchases of the construction company can generate a report needed timely, completely and accurately, so that it can be used by the management in decision-making process.